THE EVALUTION OF 2590 UPPER GASTROINTESTINAL ENDOSCOPY WERE PERFORMED IN FIRAT UNIVERCITY HOSPITAL IN THE LAST FIVE YEARS - Ali DEMİR; Osman ONAT; Ahmet YILDIRIM; Necip AYTUĞ; Oğuz AYHAN (Turkish Journal of Gastroenterology, 2020)
-